AGREEMENT IN THE DIVISION OF INHERITANCE ASSETS: PERSPECTIVES FROM MAQASID SHARIAH AND THE COMPILATION OF ISLAMIC LAW - Syamsul Bahri; eficandra eficandra; Yengki Hirawan (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
The Qur'an's Surah an-Nisa verses 11, 12, and 176, along with the hadith of Prophet Muhammad, establish the inheritance system and the share of each heir in Islam. However, in practice, many people simply agree on a division of inheritance. The reconciliation in question is mentioned in item 183 of the Compilation of Islamic Law. Therefore, this essay addresses peace in inheritance distribution from the perspective of Maqasid Sharia and its application based on KHI. Descriptive qualitative content analysis is employed in this study. The Saussure model is mentioned as the data analysis method. The analysis of relevant research materials, classification of information, interpretation of data, and verification of findings are the steps involved in analyzing research data. A credibility test is used to authenticate the data, primarily by encouraging researchers to spend more time examining crucial details from the source materials. According to the study's findings, Maqasid Sharia's emphasis on preserving the well-being of heirs is closely related to harmony in inheritance distribution. 'Takharuj', or harmony in inheritance distribution, refers to heirs' willingness to waive their rights as stipulated in the will. This willingness may occur with predetermined compensation or without any compensation at all. When peace is achieved, it occurs once each heir is fully aware of their rights under the terms of the will